2004
DOI: 10.1023/b:foop.0000044100.95918.b2
|View full text |Cite
|
Sign up to set email alerts
|

Why Should We Interpret Quantum Mechanics?

Abstract: The development of quantum information theory has renewed interest in the idea that the state vector does not represent the state of a quantum system, but rather the knowledge or information that we may have on the system. I argue that this epistemic view of states appears to solve foundational problems of quantum mechanics only at the price of being essentially incomplete.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
39
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 28 publications
0
39
0
Order By: Relevance
“…-What physically supports the information [ [515, § 6]? -How can independent reality behave for quantum mechanics to be true [6,35]?…”
Section: Information-based Approaches: Insights On Formalisms Few Onmentioning
confidence: 99%
See 1 more Smart Citation
“…-What physically supports the information [ [515, § 6]? -How can independent reality behave for quantum mechanics to be true [6,35]?…”
Section: Information-based Approaches: Insights On Formalisms Few Onmentioning
confidence: 99%
“…For some, the predictive power of quantum mechanics, allowing its use in practice, is all that matters. Others look either for a way of understanding the principles of quantum mechanics, or for what they might reveal about the world [1][2][3][4][5][6][7][8][9]. 2.…”
mentioning
confidence: 99%
“…The general principles assumed at the outset are no doubt attractive, but yet open to questioning (Marchildon, 2004). …”
Section: );mentioning
confidence: 99%
“…[1] we demonstrated that in the opposition to a rather common opinion it is possible to consider the Dirac-von Neumann formalism as a natural approximation of classical statistical mechanics. In this note we do not have any possibility to discuss different views on the problems of interpretations of quantum mechanics and the correspondence between classical and quantum theories, see, e.g., Dirac [2] or von Neumann [3]; see also, e.g., De Muynck [4], Plotnitsky [5], Marchildon [6] and Khrennikov [7] for recent discussions.…”
Section: Introductionmentioning
confidence: 99%